STUDI REAKSI SIKLOPENTILSILAN DENGAN 4-IODIDA THIOANISOL MENGGUNAKAN KATALIS PALADIUM - Aldes Lesbani; Risfidian Mohadi; Elfita Elfita (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
A study on cyclopentylsilane reaction in tetrahydrofuran with 4-iodo thioanisol has been carried out using palladium as catalyst under argon atmosphere at room temperature. The results showed that the product was tris(4-thioanisyl)cyclopentylsilane (1) which was obtained from recrystallization using methanol with the yield 35%. The Compound (1) has a melting point of 91.5-92.0 oC. Analysis using GC-MS found m/z 466 with six equivalent protons and eight carbons peak obtained from 1H and 13C NMR.